2019
DOI: 10.1097/dss.0000000000001779
|View full text |Cite
|
Sign up to set email alerts
|

OnabotulinumtoxinA for Treatment of Forehead and Glabellar Lines: Subject-Reported Satisfaction and Impact From a Phase 3 Double-Blind Study

Abstract: BACKGROUND Patient-reported outcomes are important measures of treatment benefit in facial aesthetic medicine. OBJECTIVE Evaluate prespecified subject-reported satisfaction and impact outcomes with onabotulinumtoxinA treatment of forehead lines (FHL) and glabellar lines (GL). METHODS The study randomized (3:1) 391 adults with moderate to severe FHL and GL to onabotulinumtoxinA (FHL, 20 U; GL, 20 U) or placeb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…3,4,6,[10][11][12][13][14]16,33 Only a few studies excluded patients who had received previous BT-A injections. 12,15,48 Study aims varied from evaluating the efficacy and longevity of BT-A injections in cosmetic use, to adjunctive uses, to comparisons of various formulations of BT-A. Many studies received commercial support from pharmaceutical companies manufacturing a specific toxin preparation.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…3,4,6,[10][11][12][13][14]16,33 Only a few studies excluded patients who had received previous BT-A injections. 12,15,48 Study aims varied from evaluating the efficacy and longevity of BT-A injections in cosmetic use, to adjunctive uses, to comparisons of various formulations of BT-A. Many studies received commercial support from pharmaceutical companies manufacturing a specific toxin preparation.…”
Section: Resultsmentioning
confidence: 99%
“…Earlier studies 7,9 had sparse details on study design, making results comparison difficult, if not impossible. Most studies showed that BT-A injections carried a lasting result beyond 4 months 5,7,[11][12][13][14]16 posttreatment, extending to 3 to 4 years in some cases. 6,8 The studies also included comparisons of different preparations and dilutions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Allergan also extensively monitored for immunogenicity in North American, European, and Asian patient populations, with no positive neutralizing antibody results among patients receiving up to 5 treatments of onabotulinumtoxinA. In all, Allergan conducted 8 registration studies (6 phase 3 and 2 phase 2 studies) for CFL, [8,14,16,[26][27][28][29][30] including several specifically designed for Japan and China. [28,30] Based on the neurologic exam and immunogenicity data generated from the CFL program, these assessments were not required for the subsequent FHL registration studies.…”
Section: Onabotulinumtoxinamentioning
confidence: 99%